A communicative approach towards an understanding of multi-stakeholder cross-sector collaboration as an issue field: perspectives from sustainable seafood supply chain initiatives in an emerging market - Bogie, Gillian Mary (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.